Fabrication of a Superhydrophobic RGO Coated-Polyurethan Sponge for Removing Oil, Organic Solvent, and Gasoline from Water - Thi Phuong Nhung Nguyen,; Trung Tien Phan,; Quoc Viet Dang,; Huu Thang Vuong, (Journal of Technical Education Science, 2024)
In recent years, the issue of oil and organic spillage caused by human population growth has become increasingly urgent, not only in Vietnam but also worldwide. Researchers are showing great interest in the research and development of materials capable of selectively absorbing oils and organic solvents while repelling water. In this project, an oil-absorbing material was developed using reduced graphene oxide particles incorporated into a polyurethane (PU) foam base. Utilizing PU sponge as the base material enhances the oil absorption capacity of the material. Graphene oxide was initially synthesized using the Hummers method and then reduced with ascorbic acid to form reduced graphene oxide (RGO). RGO was applied to the sponge with varying loading amounts, ranging from 0 to 254%. Subsequently, the porous material was coated with high-density polyethylene (HDPE) to assess its hydrophobicity and its ability to adsorb oil and organic solvents. The results indicate that the oil and organic solvent absorption capacity of RGO and HDPE coating materials is highest at RGO loading percentages exceeding 64%, yielding absorption rates ranging from 35 to 63 times the weight of the material. Additionally, the contact angle of RGO and HDPE coating materials is approximately 150°, demonstrating the high hydrophobicity of the material.